Top 7,000 & next 5,000 corporations the engines of economic growth business profiles 2003-2004. (Philippine Business Profiles and Perspectives, 2004)
This CD-ROM contains a database of top 12,000 corporations from 2001 to 2002, list of industry standards and company profiles. Articles and past databases of top 12,000 corporations are also included.